Avaliação de espécies forrageiras em monocultura e em integração lavoura pecuária floresta - TEIXEIRA, Maciel da Costa (2023)
The objective was to evaluate the agronomic characteristics of Tamani (Megathyrsus maximus cv. Brs tamani) and Piatã (Urochloa brizantha cv. piatã) grasses and the grain crops Corn (Zea mays) and cowpea (Vigna unguiculata) in monoculture and in Livestock Crop Integration Forest (ILPF), as well as the ingestive behavior of sheep on pasture, the dynamics of deposition and decomposition of litter and the microbial activity of the soil. A completely randomized design was used in a 2x3 factorial arrangement, with two crops: Piatã grass and Tamani grass and three systems: monoculture, integration with Cowpea and integration with corn, distributed in six treatments with six replications totaling 36 (thirty-six) units. experimental.The treatments were organized into monocultures of Piatã grass and Tamani grass and integrations of Piatã grass+Cowpea+Gliricidia; Piatã grass+corn+Gliricidia; Tamani grass+Cowpea+Gliricidia and Tamani grass+corn+Gliricidia. There was a difference in population density between the systems in both the first and second years of evaluation with 1105 and 555 tillers/m2 respectively. There was an interaction effect (P0.05) in 2022 between treatments with Cowpea. In the second year of evaluation, Cowpea in monoculture showed greater height, 27.83 cm, greater number of pods per plant 5.31, greater productivity 1134.28 kg/ha and lower weight of a thousand grains 18.6 g. In 2022, corn monoculture was superior to integrations with greater prolificacy, greater number of rows per ear 13.2, highest number of kernels per row 20.9, highest thousand weight grains and productivity with 292 g and 84.53 bags/ha respectively. In 2023 there was no difference (P>0.05) between treatments for productivity and number of grains per row. Already for the other variables, monoculture cultivation was better. The forage production of Tamani grass is severely affected in the Crop Livestock Forest Integration system. Therefore, its cultivation in a monoculture system is recommended. For the Integration system Crop Livestock Forest cultivation of Piatã grass is recommended. The cultivation of grasses both in monoculture and in crop-livestock integration, forest favors the activity soil microbial